Contempt No More. Issue 1 (January 2014) - Gagnon, Mathieu
Abstract : I have tried to show how criticism of aboriginal orthodoxy in discourse and measures taken by the current Conservative government and private commentators have set in motion a process of contempt, risking the harm associated with colonialism. Another critique of aboriginal orthodoxy, as presented by Jean-Jacques Simard, claims that First Nations are entitled to a certain level of self-government in defence of the rights of the abstract person: "it is first and foremost simply as human beings that all Amerindians possess the same rights as anyone else…." Yet this option ignores the history of First Nations' relationships with French Canadians, English Canadians and the British. While appeal to the abstract person can protect people from a threat, it cannot eliminate that threat. It seems clear that contempt towards aboriginals is still present and that their emancipation without an honourable historical justification would also lead to the exacerbation of racism against aboriginals. To make mutual recognition possible between aboriginal and non-aboriginal, we need to have shared criteria for evaluation. It would seem, therefore, that if we were willing to integrate First Nations into the Canadian constitutional order by fully recognizing them, we must find a common project. If the Canadian government were to move more in the direction of an ecological vision of development rather than in the direction of a predatory capitalism based on infinite economic growth, I believe it would be easier to secure First Nations' sense of belonging to Canada and to agree on models for joint territorial management. That awakening rings a bell we must hear: if seniority on the land and the role played by national groups in the founding of Canada are erased by a unitary, multicultural and monarchist vision of the country, the odds are high that Canadians of diverse origins will eventually suffer the blows of renewed authoritarianism and contempt.